Development of Science E-modules on Solar System Materials Based on Android for Junior High School Students - Khaerani Khaerani; Usman M; Nurmayanti Nurmayanti (Universitas Veteran Bangun Nusantara, 2023)
Solar System e-modules are electronic teaching materials that are packaged interactively to foster student motivation and enthusiasm for learning. This study aims to determine the validity and practicality of e-modules as science teaching materials for grade VII SMPN 1 Watang Pulu. The research method used is Research and Development (R&D) with the 4D research model; Define, Design, Develop, and Disseminate. Data analysis in this study is quantitative data analysis in the form of questionnaires for material and media validators as well as questionnaires for teacher and student responses. The results showed that the use of the Solar System e-module was classified as very valid to use with an overall percentage of 89.1% and the acquisition in the field test showed that the e-module met the criteria of being very practical with a percentage value of 90.8%. This states that the Solar System e-module is declared valid and practical for use in learning.